Searching and sharing of information in social networks during the different stages of a trip - Assumpció Huertas; Estela Marine-Roig (Cuadernos de Turismo)
There are three phases in the use of online social media by tourists: before, during and after the trip. The aim of this study is to determine what social network users use to find information before and during the trip, the type of information they search, and where they share information. The study also identifies the relationship this has with the trustworthiness social networks provide them, especially distinguishing the social networks managed by the destination organizations. Therefore, we conduct a survey of 800 tourists who are social network users. Results show that social networks are not a major source of information before or during the trip but are very important for sharing contents after the experience, and that the most searched information concerns the main attractions of the destination. Moreover, there is a relationship between the use of social media and their perceived trustworthiness. In this case, for those who use social networks managed by destinations, these give them greater confidence.